"Hydrothermal wrapping" with poly(4-vinylpyridine) introduces functionality: pH-sensitive core-shell carbon nanomaterials - Lawrence, K; Nelson, G; Foord, J; Felipe-Sotelo, M; Evans, N; Mitchels, J; James, T; Xia, F; Marken, F (2013)
Negatively charged carbon nanoparticles (surface-phenylsulfonated) are "wrapped" in a poly(4-vinylpyridine) cationomer and hydrothermally converted into a pH-responsive core-shell nano-composite. With a "thin shell" this nano-material (ca. 20-40 nm diameter) is water-insoluble but readily dispersed into ethanol and deposited onto electrodes. Zeta-potential measurements suggest a point of zero charge (PZC) at ca. pH 4.5 with negative functional groups dominating in the more alkaline range and positive functional groups dominating in the acidic range. XPS data suggest carboxylate and pyridinium-like functional groups. This is further confirmed in voltammetric measurements for adsorbed cations (methylene blue) and adsorbed anions (indigo carmine). The specific capacitance reaches a maximum of 13 F g-1 at the PZC explained here tentatively by a "shell charging" effect within the nanoparticle shell. This journal is © The Royal Society of Chemistry.